Jogos eletrônicos, mundos virtuais e identidade: o si mesmo como experiência alteritária - Medeiros, Márcia Duarte (2013)
This study seeks to understand the role of technological mediations in constitution of contemporary subjectivities by context of Liquid Modernity (Bauman, 2001), where the logic of consumption (Baudrillard, 1991) determines its production. With the initial question: "how to constitute the identities of players under mediation of avatar as a representation of themselves?” Or, how the experience of living as "other", being himself in video games constitutes the identities of their players”, seeks to understand the mechanisms related to issues of identity and subjectivity focusing on young individuals within a playful technological culture. A socio-historical perspective of game and cultural studies provided main theoretical references for thinking complexity of identity configurations present in situation. After a survey studies on subject, as well as an exploratory study of conditions of field, which included a quantitative survey and an immersive experience of researcher in game situation, was conducted a qualitative study of ethnographic inspiration with young people who experienced some games that they have to make choice of avatar in researcher´s presence. The results indicate use of avatars for play can be a normal shutdown conscious, giving individual a state of well being. The experience of being another (Avatar) brings a subjective desirable physical attributes such as beauty, fitness, freedom, happiness, status and social differentiation, fear and confrontation and not just cathartic possibilities (ALVES, 2005) or appeasing desires. Young players fall in an instance of ideals and lifestyles who actively participate in their processes of individuation and constitution of subjectivity. These findings point to the need for studies to examine impact of these experiences on other relational spheres of players life, as well as paving way for research into use of games as training tools for critically engaged citizens. Keywords: Electronic games; Subjectivity; Virtual Identities.